Planting wetlands and dams : [a practical guide to wetland design, construction and propagation] - Romanowski, Nick, 1954- (CSIRO Pub., 2009)
Wetland planting can bring back biodiversity, reduce the impact of drought and flood, improve water quality and conserve beauty in a mismanaged landscape. PlantingWetlands and Dams is a step-by-step, plain language guide to the creation ofconditions in which wetland plants will thrive, from design and construction tocollecting plants, seeds and propagation.Completely revised and expanded, this new edition includes comprehensiveinformation for around 200 genera of wetland plants from Tasmania to the tropics, complemented by more than 60 new colour photographs. It discusses themodification and imp.